2014
DOI: 10.1213/ane.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Ultrasound-Guided Radial Arterial Catheterization in Pediatric Patients

Abstract: Ultrasound-guided radial artery catheterization in pediatric patients was fastest and most reliable when the artery was 2 to 4 mm below the skin surface. For arteries located <2 mm below the skin surface, increasing the depth to 2 to 4 mm by subcutaneous saline injection reduced catheterization time and improved the success rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 33 publications
1
54
1
1
Order By: Relevance
“…These studies reported final success rates of 65 to 100% for ultrasound-guided techniques. 3,[12][13][14] In this study, the final success rate ranged between 88 and 100%, in agreement with the results of earlier studies and demonstrating a relatively high performance in infants, regardless of the ultrasound-guided arterial cannulation technique used.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These studies reported final success rates of 65 to 100% for ultrasound-guided techniques. 3,[12][13][14] In this study, the final success rate ranged between 88 and 100%, in agreement with the results of earlier studies and demonstrating a relatively high performance in infants, regardless of the ultrasound-guided arterial cannulation technique used.…”
Section: Discussionsupporting
confidence: 91%
“…Nakayama et al 3 suggested that ultrasound-guided radial artery catheterisation in children was fastest and most reliable when the artery was 2 to 4 mm below the skin surface. In this study, both the radial artery and posterior tibial artery were included with a mean depth of 3.1 AE 1.1 mm (range 1.4 to 6.3 mm), which was within their recommended range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases the ability to visualize the needle tip once through the skin to direct it to the vessel . Similarly, a technique using the subcutaneous injection of saline has been shown to facilitate arterial ultrasound‐guided catheterization in infants . Despite these challenges, the technique can be mastered with practice.…”
Section: Search Methodologymentioning
confidence: 99%
“…Recently Nakayama et al . improved the success rate of ultrasound‐guided radial artery catheterization in pediatric patients with superficial arteries by injecting saline to increase the depth of artery to 2–4 mm. The arteries in neonates often go into spasm during cannulation delaying blood return to the hub of the cannula.…”
mentioning
confidence: 99%